Development of E-Modules on Earth and Solar System Concepts Using SSI Approach with Embedded Islamic Values - Permana P, Niki Dian; Susilawati; Syafira, Annisa; Wati, Annisa Hikmah; Putra, Nugy Setiawan; Diniya (Proceeding International Conference on Education, 2025)
This study aims to provide a complete e-module on Islamic ideas about the earth and solar system to enhance instructional practices in schools.  This study employs the ADDIE framework for development, utilising a questionnaire as a research instrument and incorporating three expert validators: subject matter experts, media specialists, and integration specialists.  The product to be developed is an integrated e-module on Islamic concepts within the Earth and Solar System curriculum, designed for seventh-grade students in junior high and Islamic junior high schools.  The assessment outcomes indicated that the material expert achieved a score of 85%, the media expert attained 83.3%, and the integration expert received 89.5%.  The evaluation determined that the integrated e-module on Islamic concepts concerning the earth and solar system is very suitable for enhancing students' educational experiences in schools.